SNI IEC 61851-23:2014 Compliant Pre-Charge Insulation Test Setup Development in a DC EV Charger using Raspberry Pi and CAN Bus Communication Protocol - nathaniel, jevan; prajogo, tutuko; sinaga, maralo; priandana, eka rakhman; riza (Liaison Journal of Engineering, 2022)
This thesis aims to develop the system setup for the Pre-Charging Insulation Test conducted in a DC EVCS utilizing Raspberry Pi 4, DPM750/20C, and SIM100MOD, with CAN Bus communication protocol as its communication means. The problems addressed in this thesis are the rarity of the implementation of standard SNI IEC 61851- 23:2014, the studies in Pre-Charging Insulation Monitoring using integrated modules because of the low number of electric vehicles and their infrastructure, especially for DC Chargers, and the incompatibility between devices when integrating the necessary components to perform the pre-charge insulation test according to the standards. The pre-charge insulation setup is developed by integrating the Raspberry Pi 4 with 2- CH CAN HAT Module as the charge controller, DPM750/20C as the EV power module, and SIM100MOD as the ground fault detector. The setup will then perform the pre-charge insulation test procedure according to the SNI IEC 61851-23:2014. The setup development for the pre-charge insulation test has succeeded. The data obtained from the performed pre-charge insulation tests shows that the components could communicate despite the differing baud rate requirements and that the pre-charge insulation test procedure can detect the insulation faults and act accordingly in the event of ground faults. Keywords: Charging Station, Pre-Charge Insulation Test, SIM100MOD Ground Fault Detector, CAN Bus Communication, DPM750/20C Power Module, Raspberry Pi 4